1989
DOI: 10.1101/gad.3.8.1099
|View full text |Cite
|
Sign up to set email alerts
|

Notch is required for successive cell decisions in the developing Drosophila retina.

Abstract: Mutations in the Notch locus affect a variety of developmental decisions in Drosophila. In this paper, we examine the role of Notch in the developing retina. We reduced Notch activity at successive intervals during development of the retina, and then examined the effect on individual cells. When Notch activity was reduced, cells responded by selecting inappropriate developmental pathways. We found that all cell types appear to require Notch when establishing their fate. To examine further Notch's role in eye d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
300
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(310 citation statements)
references
References 29 publications
(26 reference statements)
9
300
1
Order By: Relevance
“…Loss of Notch signaling leads to ectopic life of lattice cells. 13,19 Conversely, a block in dEgfr signaling leads to ectopic death of lattice cells, whereas hyperactivation of dEgfr signaling rescues all lattice cells from death. [13][14][15][16] As we determined that apoptosis of lattice cells is spatially restricted to the death zone, we hypothesized that we could visualize changes in Notch or dEgfr signaling in lattice cells that are destined to die.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of Notch signaling leads to ectopic life of lattice cells. 13,19 Conversely, a block in dEgfr signaling leads to ectopic death of lattice cells, whereas hyperactivation of dEgfr signaling rescues all lattice cells from death. [13][14][15][16] As we determined that apoptosis of lattice cells is spatially restricted to the death zone, we hypothesized that we could visualize changes in Notch or dEgfr signaling in lattice cells that are destined to die.…”
Section: Resultsmentioning
confidence: 99%
“…13 Counteracting the dEgfr/ras pathway is the Notch signaling pathway that directs lattice cell death. 13,19 Notch is highly expressed in lattice cells. An epistasis experiment demonstrated that Notch acts to promote apoptosis by inhibiting life signaling through dEgfr.…”
mentioning
confidence: 99%
“…The conservation between the fly and vertebrates of numerous aspects of neurogenesis has lead to the speculation that lateral inhibition plays a role in mosaic formation in the vertebrate retina analogous to the role of lateral inhibition during specification and patterning of photoreceptor cells in the Drosophila ommatidia (Cagan and Ready, 1989;Baker et al, 1990;Raymond et al, 1995;Schmitt and Dowling, 1996). In the retina, lateral inhibition plays a role in the specification of early versus late neuronal cell types and has been suggested to have a second role in mosaic organization of the photoreceptor cells through maintenance of radial patterning (Ahmad et al, 1997;Austin et al, 1995;Bernardos, et al, 2005;Waid and McLoon, 1998).…”
Section: Mosaic Organizationmentioning
confidence: 99%
“…Like EGFR, the Notch receptor is used throughout Drosophila eye development (Cagan and Ready, 1989). Although its function in and around the MF has been intensely studied, less is known about its roles after R8 has been established.…”
Section: Notch Has Multiple Roles In Ommatidial Assemblymentioning
confidence: 99%